2015
DOI: 10.1016/j.scitotenv.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

An integrated assessment of two decades of air pollution policy making in Spain: Impacts, costs and improvements

Abstract: This paper analyses the effects of policy making for air pollution abatement in Spain between 2000 and 2020 under an integrated assessment approach with the AERIS model for number of pollutants (NO x /NO 2 , PM 10 / PM 2 5 , O 3 , SO 2 , NH 3 and VOC). The analysis of the effects of air pollution focused on different aspects: compliance with the European limit values of Directive 2008/50/EC for NO 2 and PM 10 for the Spanish air quality management areas; the evaluation of impacts caused by the deposition of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…A similar trend was observed for NO X emissions in Spain, with a decrease of 41% in the period 1990-2013 (MAGRAMA, 2015a). This decreasing pattern could be explained by the effects of the world economic crisis and, at the same time, by the implementation of anthropogenic NO X emission control policies (Castellanos and Boersma, 2012;Vedrenne et al, 2015). In Spain the North-Western region represents the area with the greatest decrease in NO X emissions (Cuevas et al, 2014) about 52% in the last eight years (MAGRAMA, 2015b) related to the decline in mining and industrial activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar trend was observed for NO X emissions in Spain, with a decrease of 41% in the period 1990-2013 (MAGRAMA, 2015a). This decreasing pattern could be explained by the effects of the world economic crisis and, at the same time, by the implementation of anthropogenic NO X emission control policies (Castellanos and Boersma, 2012;Vedrenne et al, 2015). In Spain the North-Western region represents the area with the greatest decrease in NO X emissions (Cuevas et al, 2014) about 52% in the last eight years (MAGRAMA, 2015b) related to the decline in mining and industrial activities.…”
Section: Introductionmentioning
confidence: 99%
“…In mountainous areas in North Spain a decrease in oxidized and reduced N depositions has been observed in response to the decrease in N emissions in recent years (Izquierdo and Avila, 2012). Nonetheless, it has been estimated that the predicted slight increase in NO X and NH 3 emissions in the next five years will produce a simultaneous increase in both oxidized and reduced N depositions (Vedrenne et al, 2015). Atmospheric N can be deposited by two processes: wet deposition, N which enters ecosystems via precipitation, and dry deposition, which is the direct input of atmospheric N gasses and aerosols by wind and gravity (Avila et al, 2010;Javid et al, 2015;Stevens et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, EPA (2011) estimates benefit-cost ratios of between 25 and 40 associated with meeting the US 1990 Clean Air Act Amendment, Pearce and Koundouri (2004) obtain benefit-cost ratios of between 1 and 18 associated with meeting the EU Registration, Evaluation and Authorisation of Chemicals (REACH) chemicals policy, and the AEA (2010) estimate benefit-cost ratios of between 12 and 37 (EU-27) and 44 and 144 (Portugal) associated with meeting the position outlined in the Thematic Strategy on Air Pollution (TSAP). Avoided external cost studies show that meeting the EU limit values of Directive 2008/50/EC (for NO 2 and PM10) in Spain (Vedrenne et al, 2015) can provide benefits of up to 5.5 M€ by 2020 (with 40% of these due to health benefits), while the implementation of emission reduction measures (including PM10, SO 2 and O 3 ) in the wider Athens area (Mirasgedis et al, 2008) are estimated to provide benefits of up to 39 M€•y −1 (with industrial sector benefits ranging between 0.1 k€•y −1 and 10 M€•y −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of reduced economic loss concentrates on wheat, potato and grapes (Vedrenne, Borge et al, 2015). In the United States, the impact of O 3 -induced crop damage was observed for maize and soybean from 1980 to 2011.…”
Section: Economic Impact Of Air Pollutionmentioning
confidence: 99%
“…Roughly 30 percent of childhood asthma within the USA is due to environmental exposures, with an associated cost of 2 billion USD per year (Roy, Sheffield et al, 2011). A Spanish study showed that a more strict regulation of the air quality resulted in a decline of the number of years lost due to PM2.5 air pollution from 230,700 in 2002, towards a predicted level of approximately 195,500 years until 2020 (Vedrenne, Borge et al, 2015). In addition, an Estonian analysis showed that air pollution results in 3859 Years of Life Lost (YLL) per year.…”
Section: Economic Impact Of Air Pollutionmentioning
confidence: 99%